Cancer Care During COVID-19 Era: The Quality of Life of Patients With Thyroid Malignancies - Falcone, Rosa; Grani, Giorgio; Ramundo, Valeria; Melcarne, Rossella; Giacomelli, Laura; Filetti, Sebastiano; Durante, Cosimo (Frontiers in Oncology, 2020)
BACKGROUND: The Covid-19 pandemic’s potential psychological impact has been widely discussed on the basis of expert opinion and previous experience with emergencies of this type. We conducted a survey of cancer patients to explore more objectively the outbreak’s impact on their emotional well-being and quality of life. METHODS: Between March 18 and April 4, 2020, at an endocrine cancer center in Rome, Italy, 137 patients were asked to complete an online 6-item questionnaire developed by our staff to explore the emotional effects of the Covid-19 outbreak in Italy (Covid-19 Emotional Impact Survey, C-19EIS). For validation purposes, we also asked participants to complete an online version of the validated Italian translation of the EORTC QLQ-C30 questionnaire. Responses were analyzed in relation to responders’ age, sex, and clinical status (advanced/metastatic disease undergoing systemic treatment versus stable metastatic thyroid cancer in active surveillance versus low-risk thyroid cancers with no evidence of structural disease during standard follow-up) RESULTS: Response rates were high (51% for the C-19EIS, 44.5% for the EORTC QLQ-C30). Overall C-19EIS scores indicated high concern over the outbreak (median 8/12). Scores were higher in women (8 [IQR 5-9] vs 6 [IQR 5-8] in men; p=0.048) and in patients <65 years (8 [IQR 5-9] vs 6 [IQR 4-8] in older patients; p=0.013). No differences emerged across clinical status groups. C-19EIS scores were inversely correlated with the EORTC QLQ-C30 Emotional function subscale (rho -0.69; p<0.001). CONCLUSIONS: There is objective evidence that the Covid-19 outbreak is causing substantial emotional distress among cancer patients, regardless of their disease severity or current health-care needs.